The Role of Sports Marketing in Customer Value - Mahmoud Al-Faraji, Hareth Muthanna; Jathir Al-Rabaiwi, Saadoun Hammoud (Journal of Economics and Administrative Sciences, 2021)
Sports marketing is one of the most important areas to attract capital and the most important economic activities at the present time and the sports field is one of the most important areas that can be used in marketing products and services and the need for sports marketing in Iraq is shown to increase the benefits and returns of sports clubs due to a lack of material resource and weakness In the available capabilities presented to it. The research problem was the lack of sufficient knowledge of the role of sports marketing in the value of the customer by members of the administrative body of Iraqi sports clubs. The research aims to know the role of sports marketing in the value of the customer in the Iraqi Premier League clubs. In order to reach this goal, two main research hypotheses were formulated that stipulated the first hypothesis (there is a correlation relationship of significant significance between sports marketing and the value of the customer) What is the second hypothesis stipulated (there is a significant correlation effect between sports marketing and the value of the customer) subjected to statistical tests, has been targeted The current research is the sports sector, and the research community was represented by members of the administrative committee of the Iraqi Premier League clubs in Baghdad. It has reached (75) members. As for the method of data collection, it was done using a questionnaire and personal interviews. The statistical program (Spss-v.23) was used to analyze the data. A set of statistical methods were also used, such as the mean, standard deviation, the coefficient of variation, the correlation coefficient of Spearman and the Alpha Cronbach coefficient. The most prominent findings of the researcher were the existence of a direct correlation relationship for sports marketing in the value of the customer, and sports marketing affects positively the value of the customer. As for the most prominent recommendations reached by the researcher, it is necessary to invest in Iraqi clubs for the positive relationship between sports marketing and customer value in order to increase profits and provide a source of self-financing for the club